A Local Wisdom-Based Campus Bazaar as a Means of Public Service Education for Students - Erinaldi Erinaldi; Muhalida Zia Ibhar; Sri Rahayu; Tiara Nabila Putri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This Community Service Program (PKM) is designed to enhance students' knowledge and practical skills in public service, while also promoting local economic empowerment through the organization of a campus bazaar that highlights local wisdom. Held at the Lancang Kuning Dumai College of Administrative Sciences, the program involved collaboration between lecturers, students, micro, small, and medium enterprises (MSMEs), and the wider community. Using a participatory approach, students played an active role in planning, implementing, and evaluating the bazaar, allowing them to apply theoretical knowledge in a real-world context. The program provided valuable hands-on experience in public service delivery, business management, and marketing, focusing on products derived from local traditions and culture. For local MSMEs, the bazaar served as an opportunity to increase product sales and expand their marketing reach, strengthening their presence in the community. The program successfully demonstrated the power of collaboration between educational institutions and local businesses in fostering economic development. By aligning academic activities with community needs, this initiative contributes to creating a sustainable local economy, emphasizing the importance of local wisdom in modern business practices.